RELIGIOUS EXISTENTIALISM OF VICTOR FRANKENSTEIN’S OBSESSION IN FRANKENSTEIN BY MARY SHELLEY - Putri, Risqi Maydia (Srawung: Journal of Social Sciences and Humanities, 2022)
The aims of this study are to analyse a classic science-fiction novel Frankenstein written by Mary Shelley using Soren Kierkergaard’s religious existentialism. The novel tells about the life journey of Victor Frankenstein as the main character. Victor Frankenstein is a genius man who is mastering science and wants to create human being from his knowledge and combine it with supernatural elements. Victor feels like he can create a creature like human. With all his ambition, he tries to build human being. Unfortunately his ambition comes into misery when his creature turns into monster. This thesis focuses on Victor Frankenstein life process. This study apply the theory of Existentialism to analyse the main point by using Soren Kierkergaard’s existentialism theory (Aesthetic, Ethic and Religious stages of life) to Victor Frankenstein Obsession, and it uses descriptive qualitative research. As the result, it finds out that Victor Frankenstein’s life existentialism was led by his obsessional character.